Child abuse sourcebook : basic consumer health information about child neglect and the physical, sexual, and emotional abuse of children, including abusive head trauma, bullying, munchausen by proxy syndrome, statutory rape, incest, educational neglect, exploitation, and the long-term consequences of child maltreatment, featuring facts about risk factors, prevention initiatives, reporting requirements, legal interventions, child protective services, and therapy options : along with information for parents, foster parents, and adult survivors of child abuse, a glossary of related terms, and directories of additional resources - Juntunen, Valarie R. (Detroit, MI : Omnigraphics, Inc., 2013)
"Provides basic consumer health information about abuse and neglect of children and adolescents, along with facts about prevention and intervention strategies and treatment for survivors of abuse. Includes index, glossary of related terms, and other resources"--Provided by publisher.
Part 7: Additional Help And Information: -- Chapter 41: Glossary of terms related to child abuse -- Chapter 42: Where to report child abuse -- Chapter 43: Directory of organizations dedicated to promoting healthy families -- Index.
Includes index.
Includes bibliographical references and index.
Keywords: Child abuse -- United States; Child abuse -- United States -- Prevention; Abused children -- United States; Abused children; Child abuse; Child abuse -- Prevention; United States; Child abuse -- United States -- Resource Guides